Penanganan Limbah Padat Polimer Dengan Cara Pembakaran Pada Combustion System Di BBIK - Rofienda Rofienda; Siti Noer Tri Hidayati (Balai Besar Kimia dan Kemasan, 1999)
The combustion of wastes as a by product of polymer industry has been conducted in various ways such as natural combustion, stiring combustion, combustion with air injection or the combination of (he aboves. It was found that the process of combustion with air injection at furnace temperature > 260 °C gives the best result, i.e. it consumes less fuel and the smallest amount of remaining solids.